Increasing E-Loyalty of E-Commerce Users Through E-Satisfaction and e-Trust - Wahid, Ayi; Vivi Afifah (International Journal of Advanced Multidisciplinary, 2023)
This study aims to prove and analyze the effect of e-service quality on e-loyalty, both directly and indirectly through e-satisfaction and e-trust of e-commerce users. The unit of analysis used was e-commerce users (Tokopedia, Shopee, Bukalapak, Lazada, Blili) in the DKI Jakarta area. The method used was a quantitative method with a sample of 200 respondents, data processing using the structural equation model method. The results of the analysis show that e-service quality directly or indirectly has a positive effect on e-loyalty through e-satisfaction and e-trust. Other results show that e-satisfaction and e-trust are partial mediating on the effect of e-service quality on e-loyalty. However, mediating e-satisfaction on the effect of e-service quality on e-loyalty has the greatest influence, when compared to the direct effect of e-service quality on e-loyalty and the indirect effect through e-trust. The research implication was an increase in e-loyalty, especially an increase in purchase intention of e-commerce users was by increasing e-satisfaction, especially increasing convenience, where e-satisfaction can be increased if e-commerce companies were able to improve e-service quality, especially increasing fulfillment of e-users commerce.